TEACHING ENGLISH TO STUDENTS WITH LEARNING DISSABILITIES - Dwi Settya Mahaputri (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
In this globalization era- English is considered as a powerful language in the world to transler information and technology. Thus, English is being a subject that must be taught on each level ofeducation in Indonesia. In teaching English. teachers should consider the differences of their students- regarding to their levels, interest, gender, abilities. cuitural. and learning disabilities. Students' with learning disabilities is being the focus of this research. Students with learning disabilities are often caught in a vicious spiral of school failure. There has been a lot of discussion around the topic of teaching English to students with learning disabilities. Students with learning disabilities have dysfunctions in processing information typically found in language-based activities. They have average or above average intelligence, but they often encounter significant problems learning how to read. write, and compute. They also may have difficulty following directions, attending to tasks. organizing assignments, and managing time. Sometimes these students appear to be unmotivated or lazy when in fact they are trying to the best of their ability. Moreover, English teachers have to think over the instruction. activity. and strategies that they r.vill use to students with leaming disabilities. Therefore, this research will discuss about teaching English to students with disabilities. more focused on strategies used by English teacher in teaching to students with learning disabilities.